CFD modelling of air and oxy-coal combustion. Issue 4 (29th April 2014) - Stęchły, Katarzyna; Wecel, Gabriel; B. Ingham, Derek
Abstract : Purpose: – The main goal of this work was the CFD analysis of air and oxy-coal combustion, in order to develop a validated with experimental measurements model of the combustion chamber. Moreover, the purpose of this paper is to provide information about limitations of the sub-models implemented in commercial CFD code ANSYS Fluent version 13.0 for the oxy-coal combustion simulations. The influence of implementation of the weighted sum of gray gas model (WSGGM) with coefficients updated to oxy-coal combustion environment has been investigated. Design/methodology/approach: – The sub-models validated with experimental measurements model for the air combustion has been used to predict the oxy-coal combustion case and subsequently the numerical solutions have been compared with the experimental data, which enclose the surface incident radiation (SIR) and the flue gas temperature. To improve the numerical prediction of the oxy-coal combustion process the own routine for calculating properties of the oxy-combustion product has been implemented. Findings: – The results of numerical simulation of combustion in the air environment fitted within the experimental measurements accuracy. However, the air combustion sub-models implemented for the oxy-coal combustion simulations does not predict the SIR within the experimental data accuracy. The implementation of own routine, which uses the coefficients calculated for oxy-coal combustion environment shows improvement in numerical prediction of oxy-coal combustion. Originality/value: – The radiative properties of gases in the combustion chamber during oxy-coal combustion calculated using the WSGGM implemented in ANSYS Fluent 13.0 do not predict the SIR within experimental measurement accuracy, however, implementation of WSGGM with updated coefficients provide a reasonable improvement in numerical prediction of SIR in the oxy-coal combustion.